The Effect of Sustainability Report Disclosure and Leverage on Stock Price Discovery Efficiency with Institutional Ownership as a Moderating Variable - Ni Nyoman Mita Asriningrum; Desak Nyoman Sri Werastuti; I Gusti Ayu Purnamawati (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
leverage on stock price discovery efficiency, as measured by price timeliness. In addition, this study examines the role of institutional ownership as a moderating variable in the relationship between ESG disclosure and leverage and stock price discovery efficiency in infrastructure sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. This research employs a quantitative approach with a causal-comparative research design. The population consists of all infrastructure sector companies listed on the Indonesia Stock Exchange, with samples selected using purposive sampling techniques. The data used are secondary data obtained from financial statements, sustainability reports, and stock trading data. Data collection was conducted through documentation. Data analysis includes descriptive statistics, classical assumption tests, and moderated regression analysis (MRA). The results indicate that ESG disclosure has a positive and significant effect on price timeliness, while leverage has a negative and significant effect. Institutional ownership strengthens the effect of ESG disclosure on price timeliness but does not moderate the relationship between leverage and price timeliness. These findings confirm that ESG transparency enhances market efficiency, whereas debt-related risk remains a dominant factor contributing to delays in stock price adjustment.